Solve Two-Step Linear Equations Quick Check%0D%0A5 of 55 of 5 Items%0D%0A%0D%0A%0D%0A%0D%0A%0D%0A%0D%0AQuestion%0D%0ASolve for x.%0D%0A3−65x=−3(1 point)%0D%0AResponses%0D%0A%0D%0Ax=5%0D%0Ax equals 5%0D%0A%0D%0Ax=6%0D%0A x equals 6%0D%0A%0D%0Ax=−5%0D%0A x equals negative 5%0D%0A%0D%0Ax=0

1 answer

To solve the equation 3 - 6x = -3, we need to isolate the variable x.

First, we can start by adding 3 to both sides of the equation to get rid of the constant term on the left side:
3 - 6x + 3 = -3 + 3

Simplifying the equation further, we have:
6 - 6x = 0

Next, we can subtract 6 from both sides of the equation to isolate the variable term:
6 - 6 - 6x = 0 - 6

Simplifying again, we get:
-6x = -6

To solve for x, we can divide both sides of the equation by -6:
(-6x)/(-6) = (-6)/(-6)

Simplifying the equation further, we have:
x = 1

Therefore, the correct answer is: x = 1.